Progonocimicids (Hemiptera, Coleorrhyncha) from the Middle Jurassic Haifanggou Formation, western Liaoning, northeast China support stratigraphic correlation with the Daohugou beds. Issue 1 (2nd January 2016) - Jiang, Jia-Qian; Cai, Chen-Yang; Huang, Di-Ying
Abstract : Jiang, J.-Q., Cai, C.-Y. & Huang, D.-Y., October 2015. Progonocimicids from the Middle Jurassic Haifanggou Formation, western Liaoning, northeast China support stratigraphic correlation with the Daohugou beds. Alcheringa 40, XXX–XXX. ISSN 0311-5518. The hemipteran suborder Coleorrhyncha includes only 37 extant species assigned to the family Peloridiidae. However, the suborder's fossil record is diverse and abundant. The extinct family Progonocimicidae is very common in Middle Jurassic strata of northeastern China, especially in the Daohugou beds of Ningcheng County, Inner Mongolia, and the Haifanggou Formation in Beipiao, Liaoning Province. We re-studied the established progonocimicid species and examined 27 new specimens, indicating that the species from Daohugou are junior synonyms of those from Haifanggou. The progonocimicids from the Haifanggou Formation are assigned to two species of Cicadocoris : C . brunneus (= Mesoscytina brunnea, = Mesocimex lini ) and C. sinensis (= Cicadocoris anisomeridis ). Both species are common in the Daohugou beds and the Haifanggou Formation. This discovery is of significance for biostratigraphic correlation of these two lithostratigraphic units. It also contributes to our understanding of the geological age of the famous Daohugou biota, which has yielded the earliest known feathered dinosaurs and diverse early mammals. Jia-Qian Jiang [jiaqianjiang@126.com ], State Key Laboratory of Palaeobiology and Stratigraphy; Nanjing Institute of Geology and Palaeontology, Chinese Academy of Sciences, Nanjing 210008, PR China; and Graduate School, University of Chinese Academy of Sciences, 19A Yuquanlu, Beijing 100049, PR China. Chen-Yang Cai [caichenyang1988@163.com ], Di-Ying Huang [dyhuang@nigpas.ac.cn ], State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology, Chinese Academy of Sciences, Nanjing 210008, PR China.